Spatial distribution and risk factors associated with Salmonella enterica in pigs - Parada, Julian (2017)
The importance of pork in the transmission of Salmonella spp. to humans has led to the development of control programmes worldwide. For this, knowledge on the epidemiology of the infection in the production system is fundamental to the efficacy of the regulations. Our objective was to determine the prevalence and spatial distribution of Salmonella-infected farms in the central region of Argentina, and to identify the predominant serotypes and epidemiological factors associated with an increased risk of infection. Salmonella was isolated from 22 of 52 sampled farms, for a farm prevalence of 42·3% (95% confidence interval 28·4–56·1). The most frequent serotypes isolated were S. Typhimurium and S. Derby, which have often been considered of public health concern in the region. Limited evidences of global and local clustering in the region under study were found, and the type of feed and presence of diarrhoeic pigs were significantly associated with having Salmonella shedders in the farm. This highlights the need to evaluate microbiological controls at the farm level, and demonstrates the usefulness of the spatial tools to identify areas of greatest risk when processing pork at slaughterhouse, which could contribute to increasing the food safety of pork products.